Respuesta :

Answer:

x = -2,  (-1 + √3 i ) / 2  ,   (-1 - √3 i) / 2.

Step-by-step explanation:

x^3 + 3x^2 + 3x + 2 = 0

f(-2) = -8 + 3*4 - 6 + 2

= -8 + 12 - 6 + 2

= 0

So (x + 2) is a factor . Dividing:

            x^2  + x  + 1

         ---------------------------------

x + 2)   x^3 + 3x^2 + 3x + 2

           x^3 + 2x^2

          ----------------

                       x^2 + 3x

                       x^2 + 2x

                        -----------

                                 x + 2

                                  x + 2.

                                 ----------

Solving  x^2 + x + 1:

   x  = [ - 1 +/- sqrt(1 - 4*1*1) ] / 2

      =  (-1 + √3 i ) / 2  ,   (-1 - √3 i) / 2.